Prevalence and risk factors of frailty in patients with gynecological malignancies after surgery and chemotherapy: a cross-sectional study - Wang, Tingting; Song, Zihe; Liu, Xianliang; Duan, Xia (Frontiers in Oncology, 2026)
PurposeFrailty is a significant factor influencing the prognosis of patients with gynecological malignancies. Surgery and chemotherapy are key components of cancer treatment; however, limited research has addressed frailty and its associated risk factors in this patient population. This study aimed to determine the prevalence of frailty and identify its associated factors in patients with gynecological malignancies following surgery and chemotherapy.MethodThis cross-sectional study was conducted at two tertiary hospitals in Shanghai between January and September 2024. Patients completed five assessment scales, including the Demographic Information Scale, Vulnerable Elders Survey-13 (VES-13), Athens Insomnia Scale (AIS), Depression Anxiety Stress Scale-21 (DASS-21), and Perceived Social Support Scale (PSSS), to screen for frailty and related factors. Multivariate logistic regression analysis was used to identify risk factors for frailty, with 95% confidence intervals (CIs) used to estimate the strength of the associations.ResultA total of 211 eligible inpatients with gynecological malignancies who had undergone surgery and chemotherapy were recruited. The prevalence of frailty in these patients was 64.9%. Multivariate logistic regression analysis identified several risk factors for frailty: older age, underweight status, stress, insomnia, married status, high white blood cell count, and low albumin levels.ConclusionThis study highlights the relatively high prevalence of frailty among patients with gynecological malignancies after surgery and chemotherapy. Understanding the factors associated with frailty is crucial for implementing timely interventions that can improve health-related quality of life and treatment outcomes in this patient population.